Возраста и коморбидетот како ризик фактори за исход кај возрасната популација со акутно бубрежно оштетување - Петронијевиќ, Звездана (Медицински факултет, УКИМ, Скопје, 2018)
Introduction: Acute kidney injury (AKI) is a complex syndrome defined as an abnormal loss of renal function that occurs over hours or days and leads to retention of end products of nitric metabolism, dysregulation of extracellular volume, and dysregulation of electrolyte homeostasis. AKI is often encountered in the adult population, the incidence of AKI is 3 to 8 times higher in the population over the age of 60, and the structural and functional changes that occur in the kidney during aging process are predisposing factors that increase the risk of AKI in elderly population. Elderly also have coexisting, comorbid diseases that increase the risk of developing AKI. The Charlson Comorbid Index (CCI) is one of the most commonly used index as a predictive method of mortality based on the classification and determination of the severity of the comorbid conditions. Design and objectives of the study: a monocentric, prospective clinical study performed to analyze the outcome of AKI in eldelry patients with respect to treatment, prognostic value estimation of Charlson's comorbid index (CCI) with respect to short and long-term outcome, identification of risk factors associated with AKI and poor outcome in an elderly population. Material and method: The study included 101 patients with an AKI age of 65 years. Patients were divided into 2 groups by age, group <75 and group> 75 years old. In terms of outcome they were divided in group with short and 90-day survival. In respect to the applied treatment they were also divided in 2 groups, a group with conservative and a group with a hemodialysis treatment. Results: The intra-hospital mortality rate in adult patients with AKI was 22.8%. The mortality rate for the 90-day follow-up period after the AKI event was 45.5%. Age was not confirmed as a risk factor for intra-hospital and 3-month outcome in patients with AKI, the average age of non-surviving patients was 74.04 ± 6.8 years versus the mean age of 73.81 ± 6.4 of surviving patients. The burden of the simultaneous presence of comorbid conditions estimated through the Charles Comorbid Index (CHI), as well as the assessment of the impact of comorbidities without age-related (CHI-1), differed un-significantly between survivors and deceased patients with AKI (p = 0.39, p = 0.28 consecutive). But Cox regression analysis confirmed the CCI score as a significant factor in survival in patients with ABO. (p = 0.036) The risk of letal outcome increases by 16.3% with each increase in this unit score.The stroke was statistically significant higher in the group of deceased patients during hospitalization with age up to 75 years compared with survivors, (34.78% vs. 14.1%) (p = 0.035) which distinguished itself as the risk factor of the outcome. Hyponatraemia and urine output, also were identified as risk factors for outcome in patients with AKI and stroke. In the group of 48 patients with cardiomyopathy, mortality rate was 56.25%, while in the 53 patients without cardiomyopathy mortality rate was 35.85% died. Cumulative survival was higher in the group of patients without cardiomyopathy - 64.2% (0.07) compared to the group of patients with cardiomyopathy- 43.8% (0.07).Cox regression analysis confirmed heart diseases as a significant prognostic factor for survival, increasing the risk of fatal outcome by about 2 times higher than patients without heart disease. Statistical analysis showed a significant difference in survival time, depending on the presence of heart disease as a comorbidity (p = 0.037). Conducted Cox regression analysis showed that HR - for heart disease, as a comorbidity, is 1.837 95% CI (1.020 - 3.306) and p = 0.043. The death rate for patients with heart disease is about 2 times higher than patients without heart disease. Out of 101 patients, 44 patients were treated conservative, of which 15 (34.09%) died, while in the group of 57 patients on hemodialysis treatment, 31 (54.39%) patients died. Cumulative survival in the group of patients treated conservatively was 65.9% (0.07), and in the hemodialysis group was 45.6% (0.06).The difference in survival time was statistically significant (p = 0.026). The Cox analysis of the results showed that hemodialysis patients had about 2 times higher risk of lethal outcome compared to patients conservatively treated, respectively, the type of treatment of AKI was confirmed as a significant predictor of survival. Cox regression analysis confirmed diuresis as a significant predictor for survival in patients with ABO (p = 0.007). HR values of 2,245 95% CI (1,251 - 4,029) indicate that the risk of lethal outcome is approximately 2.2 fold higher in the group of patients with a diuresis less than 500 milliliters compared to those with a diuresis greater than 500 milliliters. Multivariate Cox regression analysis as significant independent predictors of survival in patients with ABO confirmed the diuresis (p = 0.029) and albumin (p = 0.006). Patients with oliguria have about 2 times the risk of fatal outcome compared to patients with normal diuresis - 1.96% 95% CI (1.070 - 3.607). Increasing in serum albumin per 1 (g / l), decreased the risk of fatal outcome by 7% - 0.93 95% CI (0.884 - 0.979).In the group of patients without chronic renal disease, the average eGFR- MDRD evaluated at 90-days after AKI event, was significantly higher compared to the values at hospital discharge, with p = 0.05 (34.31 ± 19.9 vs 26.72 ± 16.3). Survival time statistics showed that the median total survival was 29.61 days. Cumulative total survival was 54.5% Conclusion: CCI score is significant independent high-risk prognostic factors for poor outcome . AKI survivors with high burden of comorbidities are at high risk for postdischarge death. Cardiomyopathy, as a risk factor, for two times increases the risk of death. Conservative treatment, increased urine output and albumin are significant predictor of survival in adult patients with acute renal injury. The presented analyzes and conclusions remain the recommendation for individual clinical approach, assessment and selection for the application of treatment taking into account the overall condition and the predicted outcome in adult patients with acute renal injury.
The age and comorbidity as risk factors for the outcome in an adult population with acute kidney injury
Докторска дисертација одбранета во 2018 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Лилјана Тозија.
Keywords: acute kidney injury, comorbidity, elderly, haemodialysis treatment